(untitled) (Journal of actual problems of jurisprudence, 2020)
Kazakhstan is a country that has committed itself to implementing the norms of the Convention on the Rights of the Child. Today, a large number of measures are being taken to protect the rights of children and ensure the rights of young people. However, according to the author and other researchers, many issues have not been properly fixed in the legislation of Kazakhstan and, accordingly, have not been implemented properly. According to the author, it is in the issues of involving young people in the political life of the country that Kazakhstan should make a big step forward. Analysis of the current state of youth policy shows that it is mainly aimed at solving social problems of young people. However, the current state of Affairs, and above all in the interests of the state, requires active involvement of young people in solving regional and national issues. In this regard, the authors believe that it is necessary to use the experience of countries that are most advanced in the study area. Finland is a country that has laid the foundations for a permanent dialogue between the state and youth. The article provides a fairly detailed analysis of the created mechanism of interaction between society, the state and an individual. The study was conducted through an analysis of Finnish legislation, which obliges educational institutions, municipalities and public authorities to take into account the views of children and young people when making decisions. A study of the built mechanism of interaction, which covers all stages of children’s growth and youth’s maturation, was conducted. This experience can be used to improve the youth policy of Kazakhstan, which requires serious improvement. Key words: children, youth, children’s rights, political rights of children, youth policy.